Glycemic control strategies and the occurrence of surgical site infection: a systematic review - Caroline Maria Herrero Domingos; Luciana Inaba Senyer Iida; Vanessa de Brito Poveda
Abstract OBJECTIVE To analyze the evidence available in the scientific literature regarding the relationship between the glycemic control strategies used and the occurrence of surgical site infection in adult patients undergoing surgery. METHOD This is a systematic review performed through search on the databases of CINAHL, MEDLINE, LILACS, Cochrane Database of Systematic Reviews and EMBASE. RESULTS Eight randomized controlled trials were selected. Despite the diversity of tested interventions, studies agree that glycemic control is essential to reduce rates of surgical site infection, and should be maintained between 80 and 120 mg/dL during the perioperative period. Compared to other strategies, insulin continuous infusion during surgery was the most tested and seems to get better results in reducing rates of surgical site infection and achieving success in glycemic control. CONCLUSION Tight glycemic control during the perioperative period benefits the recovery of surgical patients, and the role of the nursing team is key for the successful implementation of the measure.